APLIKASI PENGENALAN IKAN HIAS UNTUK PELAJAR MENGGUNAKAN TEKNOLOGI AUGMENTED REALITY BERBASIS ANDROID - Heri Purwanto; Dimas Dwi Maulana; Rudy Sofian; Rikky Wisnu Nugraha; Edi Andriansyah (Universitas Dharmawangsa, 2025)
Indonesia’s marine biodiversity requires early education, yet conventional learning media are less engaging for children. This study develops an Augmented Reality (AR)-based learning application to introduce Indonesia’s ornamental fish interactively. The application features 3D models, allowing children to engage directly with fish visualizations. The Extreme Programming (XP) method was applied with continuous iterations to ensure application quality. Black Box Testing conducted on 30 early childhood learners showed a 40% increase in learning interest compared to conventional media, along with improved understanding of marine biodiversity. The results demonstrate that this application effectively enhances children's interest in learning and raises awareness of marine conservation. Future developments may include additional features such as interactive quizzes and gamification to improve user engagement.